Konsep Butterfly Effect Dalam Pengaruh Emosi Kontrol Generasi Zoomer Dan Hasil Masa Depan Mereka - Dini, Winda Widya; adiastari, Mirza R; Raditantri, Risti; Sanjaya, Rendi David (Universitas Pahlawan Tuanku Tambusai, 2024)
The “butterfly effect” refers to a concept in chaos theory, where small events can have significant, large-scale consequences. It is described that an action or decision that seems small will have very different consequences. As a generation of Zoomers who we know are emotionally unstable, will the butterfly effect affect their life goals? Because without realizing it, small things done without careful thought will have questionable impacts in the future. Common sense cannot predict this concept, but the butterfly effect often brings delayed regret for someone who has unknowingly fallen into this concept. Unstable emotional control often provides short-lived choices based only on momentary ego, so it can be expected that these choices will lead to undesirable results.